Study and Prevalence of Orodental and Tongue Infections and Lesions Including Various Underlying Interconnected Conditions in Patients - Isha Rastogi (Recent Updates in Disease and Health Research Vol. 6, 2024)
In the dental branch, the tongue and surrounding areas, are important for several functions. Likewise any deviation in oral mucosa and tongue, its size, shape, surface, or any disease, affects dental diagnosis, treatment plan and prognosis. It’s therefore imperative to give importance to the tongue, oral mucosa and some medical dental conditions of the patient’s mouth. Here, tongue and oral mucosa with their defects and conditions are studied. They impact patients’ quality of life and dental health. The aim of this study is to assess the prevalence of tongue and oral mucosa lesions, and infections in patients with medical dental conditions. A cross-sectional study was conducted at a dental hospital in Lucknow, involving 100 patients aged between 18-75 years. Routine dental patients were screened for oral mucosa and tongue changes. The patient’s medical history and tongue plus oral mucosa changes if any, were recorded. The results showed that some tongue and oral mucosa lesions including medical conditions were very much prevalent in high numbers of patients. Few patients had no complaints. Major patients were males and over 45 years of age. These findings highlight the importance of examining the tongue and oral mucosa thoroughly especially in medical conditions. These become vital for providing appropriate treatment and care. Also, the tongue and oral mucosa changes in medical history patients have to be given significance for improving patients’ quality of life and dental oral health.